β-Secretase BACE1 Promotes Surface Expression and Function of Kv3.4 at Hippocampal Mossy Fiber Synapses - Hartmann, Stephanie; Zheng, Fang; Kyncl, Michele; Karch, Sandra; Voelkl, Kerstin; Zott, Benedikt; D'Avanzo, Carla; Lomoio, Selene; Tesco, Giuseppina; Kim, Doo Y.; Alzheimer, Christian; Huth, Tobias (Journal of Neuroscience, 2018)
The β-secretase β-site APP-cleaving enzyme 1 (BACE1) is deemed a major culprit in Alzheimer's disease, but accumulating evidence indicates that there is more to the enzyme than driving the amyloidogenic processing of the amyloid precursor protein. For example, BACE1 has emerged as an important regulator of neuronal activity through proteolytic and, most unexpectedly, also through nonproteolytic interactions with several ion channels. Here, we identify and characterize the voltage-gated K+ channel 3.4 (Kv3.4) as a new and functionally relevant interaction partner of BACE1. Kv3.4 gives rise to A-type current with fast activating and inactivating kinetics and serves to repolarize the presynaptic action potential. We found that BACE1 and Kv3.4 are highly enriched and remarkably colocalized in hippocampal mossy fibers (MFs). In BACE1-/- mice of either sex, Kv3.4 surface expression was significantly reduced in the hippocampus and, in synaptic fractions thereof, Kv3.4 was specifically diminished, whereas protein levels of other presynaptic K+ channels such as KCa1.1 and KCa2.3 remained unchanged. The apparent loss of presynaptic Kv3.4 affected the strength of excitatory transmission at the MF-CA3 synapse in hippocampal slices of BACE1-/- mice when probed with the Kv3 channel blocker BDS-I. The effect of BACE1 on Kv3.4 expression and function should be bidirectional, as predicted from a heterologous expression system, in which BACE1 cotransfection produced a concomitant upregulation of Kv3.4 surface level and current based on a physical interaction between the two proteins. Our data show that, by targeting Kv3.4 to presynaptic sites, BACE1 endows the terminal with a powerful means to regulate the strength of transmitter release.SIGNIFICANCE STATEMENT The β-secretase β-site APP-cleaving enzyme 1 (BACE1) is infamous for its crucial role in the pathogenesis of Alzheimer's disease, but its physiological functions in the intact nervous system are only gradually being unveiled. Here, we extend previous work implicating BACE1 in the expression and function of voltage-gated Na+ and K+ channels. Specifically, we characterize voltage-gated K+ channel 3.4 (Kv3.4), a presynaptic K+ channel required for action potential repolarization, as a novel interaction partner of BACE1 at the mossy fiber (MF)-CA3 synapse of the hippocampus. BACE1 promotes surface expression of Kv3.4 at MF terminals, most likely by physically associating with the channel protein in a nonenzymatic fashion. We advance the BACE1-Kv3.4 interaction as a mechanism to strengthen the temporal control over transmitter release from MF terminals.
EVALuna2:35768